Education and vocational training in Kosovo, a challenge and objective of the 21st century - Krasniqi, Safet; Sadikaj, Triumf (Edelweiss Applied Science and Technology, 2024)
Classes in Kosovo are held in private and public educational institutions. Education in Kosovo went through very hard phases and challenges especially in the years 1990/1999 since differences and the need for change made us not entirely prepared. After the establishment of Kosovo Institutions, the Department of Education and Science (DES) was established within the Ministry of Education. The primary aim was to establish the legal and professional basis as a frontline of the reform of our education system, especially the acceptance of the Bologna processes that facilitate the radical reform of general and vocational education. This paper will address the aspects of reforming and progression of vocational secondary education, vocational schools, and correspondence to the needs of the EU market and the possibility of implementing in post-secondary and university higher education.